ANALISIS KARAKTER DAN MINAT BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS 7 SMP NEGERI 1 PARANGINAN - Elda kertiasa Sihombing (Sepren, 2023)
The purpose of this study was to analyze the influence of student character and student learning interest on the mathematics learning outcomes of Grade 7 students at SMP Negeri 1 Paranginan, Humbang Hasundutan district. This study uses a quantitative approach with a survey method with a causal approach. The research sample was taken by 30 respondents. The findings obtained from this study are: 1) Student character has a positive effect on mathematics learning outcomes for Grade 7 students at SMP Negeri 1 Paranginan, Humbang Hasundutan district. This means that a positive student attitude in learning will lead to good learning outcomes, 2) Learning interest has a positive effect on Mathematics learning outcomes for Grade 7 students of SMP Negeri 1 Paranginan, Humbang Hasundutan district. This means that students' interest in learning will lead to good learning outcomes, 3) Student attitudes have a positive effect on interest in learning Mathematics for Grade 7 students of SMP Negeri 1 Paranginan, Humbang Hasundutan district.